IMPLANTATION OF STENTGRAFT BECAUSE OF AORTA RUPTURE IN POLYTRAUMA - I. M. Samokhvalov; A. N. Petrov; A. A. Erofeev; A. N. Shishkevich; A. A. Rud; M. A. Vasiliev; M. B. Borisov; N. G. Bobrovsky; S. V. Nedomolkin; K. N. Alekseev; V. A. Reva (Вестник хирургии имени И.И. Грекова)
The article describes the clinical case and analyzes the literature concerning endoprosthesis replacement in the case of traumatic thoracic aortic injury in polytrauma. Current strategy of diagnostics and treatment of patient in critical condition with rupture of isthmic aortic part is based on the principle of multistage surgical treatment (damage control orthopedic). The external fixation of multiple pelvis and extremities fractures and on-time implantation of stent-graft in thoracic aortic part were performed at first hours after the admission. A condition of the patient was stabilized. The delayed reconstructive operations on pelvis and extremities bones allowed obtaining the satisfactory functional result. The principles of staged surgical treatment and the use of on-time high-technology methods allowed saving life for the patient even in critical situation in I level traumatologic centre.